Strategic Architecture for Sustainable Halal-Certified Food MSMEs in the Digital Market Era - Isdiana Suprapti; Vegyta Irna Agustin; Resti Prastika Destiarni (Journal of Digital Marketing and Halal Industry, 2026)
The sustainability of certified halal food businesses increasingly depends on the ability of entrepreneurs to transform viral product popularity into long-term competitive advantages. This study aims to develop a strategic architecture for the growth of certified halal food businesses through internal-external environment analysis, strategic priority setting, and implementation mapping. Using a case study approach and mixed methods including observation, interviews, questionnaires, documentation, and literature review, data were analyzed with IFE and EFE matrices, IE matrix, SWOT, QSPM, and strategic architecture. The results show that the business is in a growth and build position, with internal strengths and external opportunities more dominant than weaknesses and threats. The main strategy is strengthening branding through NIB and halal certification, followed by product innovation with sweet potatoes, increasing customer loyalty, and optimizing modern technology-based production processes. The strategic architecture is planned over three years: the first year focuses on strengthening customer relationship management and human resources, the second year on developing digital marketing and financial management, and the third year on enhancing production technology and product innovation. This research confirms that halal certification is not merely about regulatory compliance but also functions as a branding tool to increase consumer trust and the competitiveness of local food businesses.